L-Vocalisation in Somerset - Garnett, Victoria Jane (Trinity College Dublin. School of Linguistic Speech & Comm Sci. C.L.C.S., 2023)
Traditional dialects in British English are undergoing a process of change, due in part to urbanisation, increased social mobility and language contact through population movement. Within British English there are several phonological changes occurring, including L- Vocalisation: the process whereby realisations of /l/ change from a Clear or Dark /l/ into a vowel sound. This process has occurred before during the Middle English period, resulting in the total deletion of /l/ in words such as talk, calf, yolk. The modern process of L-vocalisation in British English varieties appears to be the result of dialect levelling via diffusion from the South East of England. This thesis therefore asks three research questions: What is the realisation of /l/ in Somerset, what evidence is there of variation and change, and what factors (e.g., dialect levelling) are influencing these patterns? Taking influence from research into the ongoing changes throughout other British English varieties, this thesis adopts a field-study approach, conducting interviews with participants from two locations in Somerset: Central Somerset and West Somerset. These areas are selected for their contrast of urbanising space in Central Somerset and a more rural landscape found in West Somerset. Data is a combination of a reading exercise, and a more conversational interview in order to capture two registers of speech. The results and subsequent analysis find that L-vocalisation in a Coda position is in wide use throughout different areas in Somerset. In both West and Central Somerset, there is an increase in the use of vocalised forms of Coda /l/ since the time of the SED. Moreover, it finds that dialect levelling via diffusion of L-vocalisation is not universal throughout the county: rather its use reinforces and maintains existing dialect boundaries across the county, promoting the divide between the rural and the urbanising areas.
Keywords: Language change; L-Vocalisation; Dialectology; Sound change; Somerset; Sociolinguistics